Enhancing financial literacy in Malaysian preschoolers through a financial management game - Ramli, Nurhayatul Nira; Roslan, Samsilah; Sulaiman, Tajularipin; Abdul Kadir, Suhaida; Zaremohzzabieh, Zeinab; Ping, Wong Siew; Mohamad, Zulkifli (Human Resource Management Academic Research Society, 2023)
Play-based learning approaches are deemed crucial in early childhood education, particularly in preschool settings where the integration of literacy and cognitive skills significantly impacts learning outcomes. This study explores the impact of a financial management game called “Smart Money Kid” on the financial literacy of preschool students. Both descriptive and inferential analyses were employed to assess preschoolers' financial literacy levels. Results indicate that both experimental and control groups demonstrated increased literacy levels, with the experimental group exhibiting significantly higher proficiency. The findings emphasize the potential of play-based learning, specifically through a designed financial management game, in enhancing preschoolers' financial literacy.